Innovative application of graphene nanoplatelet-based ionanofluids as heat transfer fluid in hybrid photovoltaic-thermal solar collectors - I. Moulefera; J. J. Delgado Marín; A. Cascales; M. G. Montalbán; M. Alarcón; G. Víllora (Scientific Reports)
Abstract The ongoing pursuit of efficient solar thermal energy systems has driven significant interest in the development of advanced nanofluids, particularly those utilizing carbon-based nanostructures such as graphene nanoplatelets (GNP) and carbon nanotubes (CNTs). These materials, when dispersed in base fluids like water or ionic liquids, have gained attention for their tunable thermophysical properties, including thermal conductivity, viscosity, and specific heat capacity. This has positioned them as promising candidates for enhancing the thermal performance of solar collectors. However, literature examining direct experimental comparisons between the thermophysical behavior of GNP-based and CNT-based nanofluids, particularly in both water and ionic liquid media, remains sparse. Similarly, studies evaluating how such nanofluids affect the overall efficiency of solar collectors are limited and fragmented. This study investigates, for the first time, the application of GNP-based ionanofluids (INFs) in commercial hybrid photovoltaic-thermal (PVT) solar collectors. INFs were prepared using GNP and 1-ethyl-3-methylimidazolium acetate ([Emim] Ac) ionic liquid. Their thermophysical properties, including density, viscosity, thermal conductivity, and specific heat capacity, were comprehensively characterized. Long-term stability was also assessed to ensure consistent performance over time. Comparative tests with water and pure ionic liquid as base fluids revealed that INFs exhibited a significantly higher temperature rise within the collector, attributed to their lower specific heat capacity. This resulted in an exergy efficiency improvement of over 5% compared to the ionic liquid alone, underscoring the potential of INFs as advanced heat transfer fluids for high-temperature solar systems. These findings highlight the novelty of using GNP-based INFs in solar applications and pave the way for future research in optimizing nanofluid compositions for renewable energy systems.